1977
DOI: 10.1159/000214203
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Induced Release of Plasminogen Activator

Abstract: The influence of heparin and heparinoids on the release of plasminogen activator was studied in the isolated perfused pig ear. Heparin enhances the release of the tissue activator of fibrinolysis in a dose-dependent manner within the range of 0.05–1.0 IU/ml perfusion fluid. The release is also caused by sulfated polyanions at concentration of 10 μg/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 10 publications
1
33
1
Order By: Relevance
“…The mechanism by which urokinase in duces a systemic lytic state is well known and it was also established that the fibrino lytic response to urokinase is proportional to the dose [1], The mechanism of en hanced fibrinolysis by heparin deserves some discussion. It has been suggested that this effect is attained through the re lease of tissue plasminogen activator [32][33][34][35]. Since it has been observed that tis sue plasminogen activator, unlike previ ous reports [39][40][41][42][43], may induce a systemic lytic state with bleeding [44][45][46], our data may be explained if this mechanism is pos tulated.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The mechanism by which urokinase in duces a systemic lytic state is well known and it was also established that the fibrino lytic response to urokinase is proportional to the dose [1], The mechanism of en hanced fibrinolysis by heparin deserves some discussion. It has been suggested that this effect is attained through the re lease of tissue plasminogen activator [32][33][34][35]. Since it has been observed that tis sue plasminogen activator, unlike previ ous reports [39][40][41][42][43], may induce a systemic lytic state with bleeding [44][45][46], our data may be explained if this mechanism is pos tulated.…”
Section: Discussionmentioning
confidence: 59%
“…Studies in vitro failed to show any influence of heparin on the euglobulin lysis time and on the diluted clot lysis time, suggesting a lack of effect of heparin on the fibrinolytic mechanism [30], I n other studies in vitro, however, hep arin was found to have a dual effect on fi brinolysis: high concentrations inhibited lysis of preformed fibrin while low concen trations enhanced it [31]. Finally, a num ber of authors reported enhancement of fibrinolysis after intravenous administra tion of heparin [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…CY 222 also appears to have a profibrinolytic action which might operate through the activation or release of plasmin ogen-activating enzymes contained in the vascular endothelium [2]. This activity, which unfractionated heparins also manifest [12] to a lesser degree, has been demon strated indirectly in the rabbit and in healthy humans by an increase in the area of lysis of Lys-plasminogen-sensitized fibrin plates [14], This sensitization facilitates the estima tion of plasminogen activator concentrations in blood.…”
Section: Discussionmentioning
confidence: 99%
“…A HMW fraction was more active than unfractioned heparin and an LMW fraction had no in vitro effect [27]. In vivo heparin also increases the release of tissue plasminogen activator (TPA) from the vessel wall [28], The experiments with PK showed that there was no in vitro effect on fibrinolysis nor any activation o f factor XII or o f prekallikrein. After injections o f PK, however, a shortening o f the F.I.T was found.…”
Section: Discussionmentioning
confidence: 99%